THE CORRELATION BETWEEN ECONOMIC LEVEL AND CHILDBEARING AGE WOMEN’S INTEREST IN VISUAL INSPECTION WITH ACETIC ACID IN RENGEL PUBLIC HEALTH CENTER - Tri Yunita Fitria Damayanti; Warningsih Warningsih (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Cervical cancer screening is using VIA. This study was to analyze the correlation between economic level and maternal interest in VIA examinations in women of childbearing age. This was an observational quantitative analytic with a cross-sectional design research. The population was 171 women of childbearing age. The research sample was 120 according to the inclusion and exclusion criteria. The sampling technique was accidental sampling. The measuring instrument was a questionnaire. The results of the chi-square test showed that p=0.000, means that there was a correlatiom between economic level and maternal interest in VIA examinations at Rengel Tuban Health Center.